New records of water mites (Acari: Hydrachnidia) from southern Iran, with description of one new genus and three new species - Pešić, Vladimir; Smit, Harry; Asadi, Mahdieh; Etemadi, Isa (Zootaxa, 2011)
This paper deals with a collection of epigean water mites from southern Iran. One new genus, Iranobates, and three new species are described: Iranobates hesabii, Arrenurus iranicus and A. kermanensis. The following species are reported for the first time for Iran: Limnesia pinguipalpis Cook, 1967, Atractides omanensis Smit & Pešić, 2010, Neumania indentata Smit & Pešić 2010, and N. maharashtris Cook, 1967.